Analysis of the Viability of Fiscal and Monetary Policies on the Recovery of Household Consumption Expenditures Because of the Covid-19 Pandemic - Fahrul Riza; William Wiriyanata (Gorontalo State University, 2021)
The Covid-19 outbreak disrupted economic activity in almost all countries. The Indonesian economy entered a recession phase as a result of the continued contraction in economic growth in the second and third quarters of 2020. According to Keynesian economic theory, the combination of fiscal policy and monetary policy was more effective in recovering the economy from the crisis, this study aims to measure the effect of government spending, money supply, inflation and interest rates on aggregate household consumption expenditure. This study used a quantitative method, using monthly time series data from January 2015 to December 2020. The data were analyzed using the Vector Error Correction Model (VECM). The results show that government spending has a negative impact on household aggregate expenditure in the long run meanwhile interest rate has a positive impact on household consumption expenditure. Inflation do not affect aggregate household consumption expenditure, both in the short and long term. The results of the analysis are useful for evaluating the policies taken by the government to overcome the economic crisis due to the spread of the Covid-19 outbreak. The government increases aggregate expenditure to cover the decline in household aggregate consumption expenditure due to a decrease in household real income. Then expansionary monetary policy in the long run will increase aggregate demand. Therefore, the Ministry of Finance together with Bank Indonesia needs to design other policies that will have a positive impact on economic recovery in the short term. This study has not included other macro indicators that affect household consumption expenditures such as unemployment, taxes and the household marginal propensity to saving (MPS). Keywords: Household Aggregate Expenditure; Government Expenditure; Inflation; VECM